ONLINE-BASED INVESTIGATION ADMINISTRATION INPUT APPLICATION SYSTEM TO FACILITATE POLICE PERFORMANCE REPORTING NIAS RESORT - Laoli Chrisdianto Foarota; Maria Magdalena Bate’e; Kurnia Putra Bawamenewi; Idarni Harefa (Jurnal Ilmiah METADATA, 2026)
Advances in information technology are encouraging government institutions, including the police, to undertake digital transformation to support performance effectiveness and accountability. However, the investigation administration process in many police work units is still carried out manually, resulting in various problems, such as late reporting, the risk of document loss, and low investigator work efficiency. This study aims to design and implement an online-based investigation administration input application system to facilitate performance reporting at the Nias Police Resort. The methods used include user needs analysis, web-based system design, and system trials in the police work environment. The implementation results show that the system is able to accelerate the data input process, improve document accuracy and security, and provide real-time performance reports to leaders. Thus, this application system can be an effective solution to improve the efficiency, transparency, and accountability of investigation administration within the police environment.